Antioxidant Power of Tomato Seeds Measured by ESR Spectroscopy - Manin, Laura (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
Tomatoes are rich in several nutritionally valuable components, such as lycopene, β-carotene and polyphenols. During the industrial processing of tomatoes, a large amount of seeds is left behind, which is treated as biowaste. The aim of the research was to examine the antioxidant power (AP) of the seeds of two types of tomatoes – "cherry" and "apple" tomato. The measurements were carried out using the electron spin resonance (ESR) method, using the DPPH radical. This spectroscopic technique enables precise measurement of the concentration of radicals in the sample. It was monitored how the concentration of DPPH radicals decreases over time after the addition of the ethanolic extract of the seeds to the DPPH solution. The influence of seed storage temperature on AP was examined. One part of the seeds was stored at room temperature, and the other in a refrigerator at +4°C. The impact of freezing seeds at −18°C was also tested. The extracts were prepared by grinding the seeds, and then the active components were extracted by stirring in ethanol for 5 min. The samples were then centrifuged, and the liquid part was separated. Extracts were added to the ethanol solution of DPPH of known concentration and the signal loss was measured for 30 min. The results showed an approximately equal AP value of both types of tomatoes before storage. During storage at different temperatures and by freezing, there was a significant change in antioxidant activity and antioxidant capacity.